DISTALLY BASED SURAL FASCIOCUTANEOUS FLAP FOR SOFT TISSUE RECONSTRUCTION OF THE DISTAL LEG, ANKLE AND FOOT DEFECTS - Ajmal, Samira; Khan, Muhammad Ayub; Khan, Riaz Ahmed; Shadman, Muhammad; Yousof, Kanwal; Iqbal, Tariq (Journal of Ayub Medical College Abbottabad, 2009)
Background: Soft tissue management around the lower third of the leg and foot presents a considerable challenge to the reconstructive plastic surgeon. The options in this region are limited. A durable flap is the preferred option for coverage of such defects. This descriptive study was conducted at Hayatabad Medical Complex and Said Anwar Medical Centre Peshawar over a period of 4 years to evaluate the efficacy of distally based Sural flap in coverage of the lower third of leg, ankle and foot defects, in 25 patients. Methods: A descriptive study was conducted at the department of Plastic and Reconstructive Surgery at Hayatabad Medical Complex and Said Anwar Medical centre Peshawar. 25 patients with soft tissue defects over the distal leg and foot were included in this study. Distally based sural fasciocutaneous flap was used for coverage in all cases and its survival, successful coverage of the defect and donor site morbidity studied. Results: Out of 25 flaps, 20 showed complete survival (80%). Partial flap loss was found in 2 patients (8%), marginal flap necrosis in 2 patients (8%) and complete loss in 1 patient (4%). Conclusions: The distally based sural flap is a versatile and reliable flap for the coverage of soft tissue defects of the distal lower extremity. The procedure is done as a single stage; the dissection is easy with short operating time and minimal morbidity. Key Words: Distally based Sural flap; distal leg, heel and foot defects; reconstruction of foot